The large subunit of RNA polymerase II is a substrate of the Rsp5 ubiquitin-protein ligase - Huibregtse, Jon M. (The National Academy of Sciences of the USA, 1997)
The E3 ubiquitin-protein ligases play an important role in controlling substrate specificity of the ubiquitin proteolysis system. A biochemical approach was taken to identify substrates of Rsp5, an essential hect (homologous to E6-AP carboxyl terminus) E3 of Saccharomyces cerevisiae. We show here that Rsp5 binds and ubiquitinates the largest subunit of RNA polymerase II (Rpb1) in vitro. Stable complex formation between Rsp5 and Rpb1 was also detected in yeast cell extracts, and repression of RSP5 expression in vivo led to an elevated steady-state level of Rpb1. The amino-terminal domain of Rsp5 mediates binding to Rpb1, while the carboxyl-terminal domain of Rpb1, containing the heptapeptide repeats characteristic of polymerase II, is necessary and sufficient for binding to Rsp5. Fusion of the Rpb1 carboxyl-terminal domain to another protein also causes that protein to be ubiquitinated by Rsp5. These findings indicate that Rsp5 targets at least a subset of cellular Rpb1 molecules for ubiquitin-dependent degradation and may therefore play a role in regulating polymerase II activities. In addition, the results support a model for hect E3 function in which the amino-terminal domain mediates substrate binding, while the carboxyl-terminal hect domain catalyzes ubiquitination of bound substrates.